The “CMT rat”: peripheral neuropathy and dysmyelination caused by transgenic overexpression of PMP22 - Niemann, Stephan; Sereda, Michael W.; Roßner, Moritz; Stewart, Helen; Suter, Ueli; Meinck, Hans-Michael; Griffiths, Ian R.; Nave, Klaus-Armin (Annals of the New York Academy of Sciences, 1999)
We have generated a transgenic rat model of Charcot-Marie-Tooth disease type 1A (CMT1A) providing formal proof that this neuropathy can be caused by increased expression of peripheral myelin protein-22 (PMP22). Heterozygous PMP22-transgenic rats develop muscle weakness and gait abnormalities as well as reduced nerve conduction velocities and EMG abnormalities, which closely resemble recordings in patients with CMT1A. Dys- and demyelination, Schwann cell hypertrophy, and “onion bulb” formation are also similar to findings in humans. When bred to homozygosity, transgenic rats completely fail to elaborate myelin, but all myelin-forming Schwann cells segregate with axons in the normal one-to-one ratio. Although arrested at this “promyelin” stage, differentiation proceeds in homozygous rats at the molecular level, as demonstrated by high-level expression of myelin structural genes. Intracellular trafficking of the wild-type protein is not visibly impaired, even when strongly overexpressed, suggesting that PMP22 blocks myelin assembly in a late Golgi/cell membrane compartment of the affected Schwann cell.